Pengaruh Pengendalian Internal, Moralitas Individu dan Perilaku Tidak Etis Pada Kecenderungan Kecurangan Akuntansi - Agus Defri Yando; Mortigor Afrizal Purba (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This research aimed to determine the effect of internal control, individual morality, and unethical behavior to the tendency of accounting fraud. The theory used in this research are the Agency Theory and Theory Of Planned Behavior. The population in this study is staff accounting department property company in Batam region. This study using purposive sampling technique. These samples were taken are as many as 34 staff accounting. The Collected data using by questionnaires. The data analysis technique used in this research is multiple linear regression. The results of this research showed that the internal control, individual morality, and unethical behaviorhave negatively affect of tendency of the accounting fraud at the property company in Batam region